Gaya Kepemimpinan Inovatif Progresif Pemerintah Desa dalam Pengambilan Keputusan Penyusunan APBDes - Romsa Endrekson (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
Village Government or also called Pemdes is a government agency tasked with managing village-level regions. This study aims to determine and analyze the influence of the progressive innovative leadership style of the village government on decision making in the preparation of the APBDes in Karangan Village, Rambang Kapak Tengah District, Prabumulih City. Primary data collection was carried out by distributing questionnaires and interviews to 90 respondents from 837 population representatives from the village government, community leaders, religious leaders, traditional leaders, women's groups and youth groups in Karangan Village, while secondary data was carried out with a literature review. The method used to analyze data is simple linear regression. The results of the analysis show that independent variables (leadership style) do not show a strong influence on the dependent variable (decision making) through testing the analysis of the coefficient of determination (R2). In addition, the results of the study also showed that the progressive innovative leadership style of the village government had no effect on decision making in the preparation of the APBDes in Karangan Village, Rambang Kapak Tengah Subdistrict, Prabumulih City. This can happen because the leadership style adopted by the Karangan village government prior to Law No. 6/2014 has applied leadership to open the widest possible participation space for the community to participate in transparent and accountable village development planning which later becomes a characteristic of the leadership style innovative progressive. Keywords: Leadership Style, Decision Making